Paper 41: Suture-Bridge Fixation of Osteochondral Fractures and Osteochondritis Dissecans in the Knee: Excellent Rates of Early Lesion Stability and Osseous Union. Issue 7 (30th July 2022) - Ellis, Henry; Wyatt, Charles; Johnson, Benjamin; Cooper, Savannah; Carpenter, Connor; Wilson, Philip
Objectives: Preservation of articular cartilage in the setting of acute or chronic injury in the knee is paramount for long-term joint health. Achieving osseous union, minimizing implant related injury, and eliminating the need for reoperation for osteochondral fracture lesions (OCL) and osteochondritis dissecans (OCD) remain a challenge for the orthopedic surgeon. To evaluate osseous and chondral integration following a suture and non-metallic anchor (suture-bridge) construct utilizing magnetic resonance imaging (MRI). A secondary purpose was to assess the outcomes and short-term complications of suture bridge fixation of OCL and OCD in the knee. Methods: Consecutive patients (n=39, 41 knees) treated within a single academic sports medicine institution who underwent suture-bridge fixation of an OCL or OCD of the knee from initiation of the technique in 10/2019 through 03/2021 were reviewed with IRB approval. The suture-bridge technique employed 1.5 or2.9mm bioabsorbable knotless anchors (avg n= 3.93; 3-6) placed on the outside margins of the lesion with multiple strands (2-8) of hand-tensioned absorbable (87.5%; #0 or #1Vicryl) or non-absorbable (2-0 braided polyester) bridging suture. A minimum of six months follow up to assess bony union was required for inclusion, resulting in 40 knees in 38 patients available for study. Demographics, pre-operative MRI lesion characteristics, including lesion type (OCL vs OCD), presence of bone in within the fragment, size, and location, were documented. Healing was assessed by radiographs and MRI, with MRI obtained on all OCDs and any chondral-only OCL lesions. MRI was available on 33/40 (82.5%) knees within one year of surgery and was rated for lesion healing: Full Union = 100% cancellous or cancellous-chondral lesion continuity, Stable Union = >50% continuity with some fibrous tissue present, Un-united = < 50% continuity and extensive fibrous signal or fluid below the lesion. Complications, and rates and timing of return to sport (RTS) were evaluated. For assessment of early pain and functional improvement in the setting of isolated osteochondral treatment (without confounding concurrent patellar instability, or other treatment in conjunction with OCL), KOOS patient reported outcomes were analyzed in the OCD cohort at 6 and 12 months. Results: 33 (82.5%) of all lesions demonstrated Full Union and no lesions failed treatment. MRI assessment of healing (5.8 months; 3-12 months) demonstrated 9 (64.3%) OCDs with Full union, 5 (35.7%) OCDs with Stable union, and none un-united (Figure 1); while OCLs demonstrated 17 (89.5%) with Full union, 2 (10.5%) with Stable union, and none un-united. (Figure 2) All 7 bony OCL without an MRI demonstrated radiographic union. 30 (75%) lesions returned to sports at an average of 6.5 months (3.8-10.2). KOOS Daily Living, Pain, Quality of Life, and Symptom scores all demonstrated significant improvement from baseline at 6months and 1 year. (Table 2). There were 2 (5%) complications consisting of re-operation for marginal chondroplasty on otherwise stable lesions, and no re-operations for failure or revision of the suture-bridge construct. Conclusions: In this series of OCL and OCD of the knee, suture-bridge fixation demonstrates excellent rates of MRI and radiographic union and good early outcomes with minimal short-term complications. This technique may be utilized for lesion salvage as preferred over loose body removal and marrow-stimulation and may have significant benefits in comparison to metallic and non-metallic screw/tack constructs in the treatment of these challenging lesions. Longer term follow-up and investigation is warranted. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/96288f30-99be-431a-9937-0218d3245043/1/Suture_Bridge_AbstractAOSSMFinalfigures.docx